Communitarian cooperative organic rice farming in Hongdong District, South Korea. (February 2015) - Suh, Jungho
Abstract: It is often questioned whether sustainable agriculture by smallholder farmers can phase out conventional agriculture. This paper draws on a case study of organic rice farming in Hongdong District, South Korea, and provides insights into communitarian cooperative organic farming, a collective organic farming model. Various organic farming practices (e.g. integrated rice–duck farming) have been collectively adopted by small-scale rice farmers in Hongdong since 1994. Organic rice farming in Hongdong is characterised by place-based cooperatives, community-supported agriculture, and strong community leadership. Hongdong has demonstrated that communitarianism and smallholder cooperatives can work for each other complementarily and therefore that communitarian organic farming through smallholder cooperatives is highly operational. The Hongdong organic farming model is of great relevance to other parts of rice-growing Asia, which are dominated by smallholding farmers, in terms of the twin goals of food security and food safety. Highlights: Communitarianism can co-exist with any type of property rights regime. Communitarianism and capitalist cooperatives are complementary to each other. Communitarian organic farming through smallholder cooperatives is operational. Communitarian cooperative organic farming is a pathway to rural development in Asia.